The Three-Level Model (3LM): A Conceptual Framework for the Integration of Naqli and Aqli Knowledge In Medicine - Razrim Rahim; Mohd Rushdan Mohd Jailani; Mohd Faisal Mohamed; Affirul Chairil Ariffin (Kulliyyah of Medicine, International Islamic University Malaysia, 2024)
Indexed by WOS/Scopus/MyCite